Substitution in Differential Equation

Calculus Level 2

d 2 y d x 2 = 1 + 2 ( 1 + y ) 1 + y 2 ( d y d x ) 2 \dfrac{d^2y}{dx^2}= 1+ \dfrac{2(1+y)}{1+y^2}\left(\dfrac{dy}{dx}\right)^2 Let y = tan z y=\tan z . Then the differential equation above becomes d 2 z d x 2 = cos 2 z + k ( d z d x ) 2 \dfrac{d^2z}{dx^2}= \cos^2z+ k\left(\dfrac{dz}{dx}\right)^2 for some constant k k . Find the value of k k .

0 2 1 -1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Noah Hunter
Sep 7, 2016

Knowing that y = tan z y=\tan { z } , differentiating it w.r.t. x ,

d y d x = sec 2 z d z d x \frac { dy }{ dx } =\sec ^{ 2 }{ z } \frac { dz }{ dx }

Differentiating it again w.r.t. x ,

d 2 y d x 2 = 2 sec 2 z tan z ( d z d x ) 2 + sec 2 z d 2 z d x 2 \frac { { d }^{ 2 }y }{ d{ x }^{ 2 } } =2\sec ^{ 2 }{ z } \tan { z } { \left( \frac { dz }{ dx } \right) }^{ 2 }+\sec ^{ 2 }{ z } \frac { { d }^{ 2 }z }{ d{ x }^{ 2 } }

d 2 y d x 2 = sec 2 z [ 2 tan z ( d z d x ) 2 + d 2 z d x 2 ] \frac { { d }^{ 2 }y }{ d{ x }^{ 2 } } =\sec ^{ 2 }{ z } \left[ 2\tan { z } { \left( \frac { dz }{ dx } \right) }^{ 2 }+\frac { { d }^{ 2 }z }{ d{ x }^{ 2 } } \right]

Substituting into the original equation,

sec 2 z [ 2 tan z ( d z d x ) 2 + d 2 z d x 2 ] = 1 + 2 ( 1 + tan z ) 1 + tan 2 z ( sec 2 z d z d x ) 2 \sec ^{ 2 }{ z } \left[ 2\tan { z } { \left( \frac { dz }{ dx } \right) }^{ 2 }+\frac { { d }^{ 2 }z }{ d{ x }^{ 2 } } \right] =1+\frac { 2\left( 1+\tan { z } \right) }{ 1+\tan ^{ 2 }{ z } } { \left( \sec ^{ 2 }{ z } \frac { dz }{ dx } \right) }^{ 2 }

Simplifying the terms,

2 tan z ( d z d x ) 2 + d 2 z d x 2 = cos 2 z + 2 ( 1 + tan z ) sec 2 z sec 4 z ( d z d x ) 2 1 sec 2 z 2\tan { z } { \left( \frac { dz }{ dx } \right) }^{ 2 }+\frac { { d }^{ 2 }z }{ d{ x }^{ 2 } } =\cos ^{ 2 }{ z } +\frac { 2\left( 1+\tan { z } \right) }{ \sec ^{ 2 }{ z } } \sec ^{ 4 }{ z } { \left( \frac { dz }{ dx } \right) }^{ 2 }\frac { 1 }{ \sec ^{ 2 }{ z } }

2 tan z ( d z d x ) 2 + d 2 z d x 2 = cos 2 z + 2 ( 1 + tan z ) ( d z d x ) 2 2\tan { z } { \left( \frac { dz }{ dx } \right) }^{ 2 }+\frac { { d }^{ 2 }z }{ d{ x }^{ 2 } } =\cos ^{ 2 }{ z } +2\left( 1+\tan { z } \right) { \left( \frac { dz }{ dx } \right) }^{ 2 }

d 2 z d x 2 = cos 2 z + 2 ( 1 + tan z tan z ) ( d z d x ) 2 \frac { { d }^{ 2 }z }{ d{ x }^{ 2 } } =\cos ^{ 2 }{ z } +2\left( 1+\tan { z } -\tan { z } \right) { \left( \frac { dz }{ dx } \right) }^{ 2 }

Hence, d 2 z d x 2 = cos 2 z + 2 ( d z d x ) 2 \frac { { d }^{ 2 }z }{ d{ x }^{ 2 } } =\cos ^{ 2 }{ z } +2{ \left( \frac { dz }{ dx } \right) }^{ 2 }

k = 2 \boxed{k = 2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...